DAMPAK RESPON LINGKUNGAN BERBELANJA TERHADAP PERILAKU PEMBELIAN IMPULSIF PADA BLOSSOM FACTORY OUTLET - Raeni Dwi Santy (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
Business in this globalization era has became a challenge for every business world to increase their performance and the business‟ quality to hold them in a big competition. The way to take over the market share is by depending our customer. Every entrepreneurs are faced with a harder life challenge in operating their business to survive their company and they can develop their business which has been operated for a longtime. And if this situation is connected with the customer buying behavior , so the company have to pay attention the other environment. The capability of spending money make a person feel to have a power. Sometimes the customer doesn‟t feel uncertainly with their decision in buying a product and asking for a help from the other person to choose about the product which want to be bought.The research of this study are: (1) to assess the responses of respondent regarding Blossom Factory Outletstore environment . (2) to assess the impulsive buying behavior of Blossom Factory Outlet. (3) to know how big about the impact of store environment toward impulsive buying behavior at Blossom Factory OutletThe method which is used in this research is descriptive and verification methods with a sample of 100 people who are the visitors of Blossom Factory Outlet, and using linear regression analysis to determine the mathematical model, the product moment correlation analysis (pearson) for calculating the level of closeness of relationship, determination analysis to know about the effect. the author use SPSS 13.0 version for windows to facilitate in the data processing. The results of this research can be found with a simple linear regression equation is Y = 93.894 + 1.499 X. The correlation between store environment with Impulsive buying behavior is strong and has a positive relationship. The magnitude of store environment impact toward the impulsive buying behavior is 43.9% and the balance of 56.1% was influenced by the other factors which are not examined by author such as (1)The product price which is demanded, (2) Service quality for the consumer , (3) intense competition in the same business world. Thus the better store environment will increasingly impact on the level of impulsive buying behavior .Key words : Store Environment ,impulsive buying, customer behaviour